(untitled) (Editora Impacto Científico, 2025)
The present paper offers an essay on the role of imaginary in shaping the school culture to school autonomy, or autonomy for a school, whose foundations are thinking of D. Julia, C. Castoriadis and M. Bakhtin, and concludes that the importance of utopia in school as a space of their own knowledge, be built collectively.